2021
DOI: 10.3390/ijms22168356
|View full text |Cite
|
Sign up to set email alerts
|

Concepts of Regeneration for Spinal Diseases in 2021

Abstract: It is our pleasure to announce the publication of the Special Issue “Regeneration for Spinal Diseases” in the International Journal of Molecular Sciences (IJMS, ISSN 1422-0067) [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…The latest studies have shown that an estimated 103 million people worldwide are affected by DSD, while in the US, ~600 000 patients with lumbar spinal stenosis undergo operations each year 4 6 . For severe DSD, surgical resection and/or fusion are the primary treatment, especially in patients with neurological symptoms 7 9 . However, although surgery can effectively alleviate the symptoms of patients in a timely manner, some postoperative adverse events are inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…The latest studies have shown that an estimated 103 million people worldwide are affected by DSD, while in the US, ~600 000 patients with lumbar spinal stenosis undergo operations each year 4 6 . For severe DSD, surgical resection and/or fusion are the primary treatment, especially in patients with neurological symptoms 7 9 . However, although surgery can effectively alleviate the symptoms of patients in a timely manner, some postoperative adverse events are inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal diseases have gradually become one of the primary health concerns, with patients typically undergoing spinal surgery to alleviate pain and improve functionality, but with a high risk of postoperative infection. 26 , 27 The incidence rate of post‐spinal surgery wound infection ranges from 0.2% to 16.1%, averaging 3.1%. 28 Postoperative infections can cause difficult‐to‐heal wounds, prolonged hospital stays, increased mortality and endanger patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Spine-related diseases place a heavy financial and psychological burden on the general population ( 1 ). These diseases include discogenic low back pain (DLBP) ( 2 ), lumbar disc herniation ( 3 ), lumbar disc degeneration ( 4 ), spinal cord injury ( 5 ), ligament injury ( 6 ), and sacroiliac joint disease ( 7 ).…”
Section: Introductionmentioning
confidence: 99%